(untitled) (Biological Sciences - PJSIR, 2002)
Sunflower (Helianthus annus) stems were subjected to organosolv delignification with acetic, formic and propionic acids. It was found that, among lower aliphatic organic acids, only acetic acid sufficiently delignified this raw material. The kinetics of delignification process was also studied and it was established that optimum acetosol v delignification was achieved with 95% acetic acid, and 0.25% hydrochloric acid as catalyst in 90 min of fractionation time. Further data on measurement and classification of fiber dimensions of this raw material showed the absence oflong fibres and abundance of short fibres in the pulp.